NILAI BUDAYA FLORES DALAM NOVEL IKHTIAR CINTA DARI ADONARA KARYA J.S. MAULANA - Rini Widiastuti; Salmah Djirong (TELAGA BAHASA, 2022)
A novel is an imaginary literary work that contains a series of stories that tell a picture of human life in relation to others and in a community so that it can create a deep impression for the reader. This situation seems to bring the reader into the life story of a novel, especially if the novel is closely related to local culture. As for the focus of this research, what are the cultural values of Flores contained in the novel Ikhtiar Cinta dari Adonara? The method used in this research is descriptive using note taking techniques, interviews, and literature study. The results of this study indicate that there are seven Flores cultural values in the novel Ikhtiar Cinta dari Adonara (1) Religious and Belief Systems, (2) Social Systems and Organizations, (3) Knowledge Systems, (4) Language, (5) Arts, ( 6) Livelihood System, (7) Technology System and Equipment.